Tuning the C2/C1 Hydrocarbon Separation Performance in a BioMOF by Surface Functionalization. Issue 39 (23rd July 2019) - Huang, Yong‐Liang; Qiu, Pei‐Li; Zeng, Heng; Liu, Huan; Luo, Dong; Li, Yan Yan; Lu, Weigang; Li, Dan
Abstract : Solvothermal reaction of adenine, 1, 3, 6, 8‐tetrakis( p ‐benzoic acid)pyrene (H4 TBAPy), and Zn(NO3 )2 in DMF afforded a three‐dimensional anionic bioMOF 1 . It features one‐dimensional tubular channels with exposed Watson–Crick faces and nitrogen‐rich purines, which endows 1 with multiple adsorption sites on its polar surface, translating into high selectivity of C2 hydrocarbons over C1. Moreover, an isostructural bioMOF 1‐NH2 was synthesized by using 2‐aminoadenine in place of adenine, resulting in additional amine groups pointing toward the channel cavity. The added strong adsorption sites have been demonstrated to be able to further increase the selectivity of C2 hydrocarbons over C1. Abstract : Two isostructural anionic 3D bioMOFs (1 and 1‐NH2 ) were synthesized. Both of them feature 1D channel with accessible Watson–Crick sites and purine‐decorated surface. Gas adsorption studies demonstrate pore surface functionalization is an effective approach to improve the adsorption capacity and gas selectivity, particularly for the more polarizable gases. The selectivity of 1‐NH2 is higher for CO2 and C2 hydrocarbons than for CH4 .